Description of Pseudomonas gregormendelii sp. nov., a Novel Psychrotrophic Bacterium from James Ross Island, Antarctica - Kosina, Marcel; Švec, Pavel; Černohlávková, Jitka; Barták, Miloš; Snopková, Kateřina; De Vos, Paul; Sedláček, Ivo (Current microbiology, 2016)
During the microbiological research performed within the scope of activities of Czech expeditions based at the Johann Gregor Mendel Station at James Ross Island, Antarctica, two psychrotrophic gram-stain negative non-fluorescent strains CCM 8506T and CCM 8507 from soil were extensively characterized using genotypic and phenotypic methods. Initial characterization using ribotyping with HindIII restriction endonuclease and phenotyping implies that both isolates belong to a single Pseudomonas species. Sequencing of rrs, rpoB, rpoD and glnA genes of strain CCM 8506(T) confirmed affiliation of investigated strains within the genus Pseudomonas. Further investigation using automated ribotyping with EcoRI (RiboPrinter(®) Microbial Characterisation System), whole-cell protein profiling using the Agilent 2100 Bioanalyzer system, extensive biochemical testing and DNA-DNA hybridization experiments confirmed that both investigated strains are members of a single taxon which is clearly separated from all hitherto described Pseudomonas spp. Based on all findings, we describe a novel species Pseudomonas gregormendelii sp. nov. with the type strain CCM 8506(T) (=LMG 28632T).
Keywords: Bacterial Proteins; Pseudomonas; Soil Microbiology; RNA, Ribosomal, 16S; RNA ribozomální 16S; Antarktida; půdní mikrobiologie; DNA, Bacterial; DNA, Ribosomal; bakteriální proteiny; fylogeneze; Phylogeny; ribozomální DNA; Antarctic Regions; DNA bakterií